Public Utilities and the Income Tax - Bernstein, E. M. (Quarterly Journal of Economics, 1931)
Journal Article Public Utilities and the Income Tax Get access E. M. Bernstein E. M. Bernstein North Carolina State College Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 45, Issue 3, May 1931, Pages 529–535, https://doi.org/10.2307/1883904 Published: 01 May 1931